Fine-scale analysis reveals a potential influence of forest management on the spatial genetic structure of Eremanthus erythropappus - Rocha, Lucas Fernandes [UNESP]; Paula, Natália Ribeiro de; De Carvalho, Dulcinéia (Springer Nature, 2020)
Forest management may have significant effects on forest connectivity and natural population sizes. Harvesting old-growth single trees may also change natural patterns of genetic variation and spatial genetic structure. This study evaluated the impacts of forest management using a silvicultural system of seed trees on the genetic diversity and spatial genetic structure of Eremanthus erythropappus (DC.) MacLeish. A complete survey of 275 trees on four plots was undertaken out to compare the genetic variation of a managed stand with an unmanaged stand. We genotyped all adult and juvenile individuals 60 months after the management and compared the genetic diversity and the spatial genetic structure parameters. Genetic diversity was considered high because of an efficient gene flow between stands. There were no genetic differences between stands and no evidence of inbreeding. Genetic clustering identified a single population (K = 1), indicating no genetic differentiation between managed and unmanaged stands. Adult and juvenile individuals of the unmanaged stand were more geographically structured than individuals from the managed one. There was a tendency of coancestry among juveniles at the first class of distance of the managed stand, suggesting a drift of genetic structure possibly caused by management. Understanding early responses to management on genetic diversity and stand structure is a first step to ensuring the effectiveness of conservation practices of tree species. The sustainability of forest management of E. erythropappus on genetic diversity, and more accurately, on spatial genetic structure needs evaluation over time to promote effective conservation of the population size and genetic variability.
Keywords: Brazilian Cerrado; Gene flow; Genetic diversity; Microsatellite markers; Silvicultural management